Milk marketing options for the dairy farmers in open economy and their choice in Tamil Nadu, India - Thirunavukkarasu, D.; Sudeepkumar, N.K. (2005)
In the study area predominantly three marketing options were available for the dairy farmers; unorganized vendors, formal / organized dairy cooperatives and integrated contract system. A majority of dairy farmers around 57.3 percent had shifted from one marketing option to another. The rest 42.7 per cent of dairy farmers remained in the same marketing option from the day they began commercial milk production. A major shift from vendors (informal system) to contract (39.5 per cent), followed by vendor to co-operative (24.4 per cent) and co-operative to vendor (19.8 per cent) was noticed. Irregularity in payment and stoppage of procurement by vendor system made dairy farmers shift from vendor system to others. After the weakening of vendor- farmer relationship and initiation of Milk Producer Cooperatives at the village level, there has been a shift from vendor to co-operative system. When the dairy sector opened for private investment coupled with poor performance of cooperatives, farmers shifted towards new marketing option the 'integrated contract system'. Irregularity in payment, distant location of collection centre and inability to milk the animals were reasons for shifting back to vendor from other marketing options. Prompt payments, sustainability of marketing systems in business were major factors responsible for retaining members and attracting new dairy farmers. Dairy farmers with the experiences of various marketing options gave more value to the prompt payment for the milk sold on comparing to milk prices.